Republic of Mozambique : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the Republic of Mozambique's Poverty Reduction Strategy Paper (PRSP) Progress Report. The paper presents the national macroeconomic setting and describes the main economic policy measures for 2001 and 2002. It evaluates the process of integrating the Plan for the Reduction of Absolute Poverty (PARPA) into annual planning instruments and the monitoring and evaluation process. The government's performance in the fundamental action areas is discussed. The paper also describes the trends of the main sectoral indicators, and compares the results obtained by these sectors with the corresponding PARPA targets.